Development and formation of wing cuticle based on transcriptomic analysis in Locusta migratoria during metamorphosis - Jing Zhang; Zhaochen Wu; Shuo Li; He Huang; Suning Liu; Weimin Liu; Xiaoming Zhao; Jianzhen Zhang (Journal of Integrative Agriculture, 2024)
Wings are an important flight organ of insects. Wing development is a complex process controlled by a series of genes. The flightless wing pad transforms into a mature wing with the function of migratory flight during the nymph-to-adult metamorphosis. However, the mechanism of wing morphogenesis in locusts is still unclear. This study analyzed the microstructures of the locust wing pads at pre-eclosion and the wings after eclosion and performed the comparative transcriptome analysis. RNA-seq identified 25,334 unigenes and 3,430 differentially expressed genes (DEGs) (1,907 up-regulated and 1,523 down-regulated). The DEGs mainly included cuticle development (LmACPs), chitin metabolism (LmIdgf4), lipid metabolism-related genes, cell adhesion (Integrin), zinc finger transcription factors (LmSalm, LmZF593 and LmZF521), and others. Functional analysis based on RNA interference and hematoxylin and eosin (H&E) staining showed that the three genes encoded zinc finger transcription factors are essential for forming wing cuticle and maintaining morphology in Locusta migratoria. Finally, the study found that the LmSalm regulates the expression of LmACPs in the wing pads at pre-eclosion, and LmZF593 and LmZF521 regulate the expression of LmIntegrin/LmIdgf4/LmHMT420 in the wings after eclosion. This study revealed that the molecular regulatory axis controls wing morphology in nymphal and adult stages of locusts, offering a theoretical basis for the study of wing development mechanisms in hemimetabolous insects.